Improving Class III Learning Outcomes in Indonesian Language Learning Elaborating Directional Texts at SDN Krasak 01 - Astuti, Luki Puji (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
The author's experience in learning Bahasa Indonesia theme 6 sub-theme 2 in Indonesian language learning on basic competencies outlines the text of instructions on animal and plant care, in grade 3 of Sdn Krasak 01, Brebes district, lesson year 2019/2020. Showing that students' mastery of Bahasa Indonesia subject matter theme 6 sub-theme 2 is still low.of 16 students, 6 (43.75%)experienced completion of learning and the rest have not completed the study of 10 students (56.25%). Based on the description above, the authors carry out the research. By making efforts to improve learning by focusing on discussion methods with contextual approaches to improve students' achievements and activities in indonesian language learning. The result of improvement in cycle 1 of learning completion rose to 62.5%. In cycle II 79.37%. From these results it appears that students' learning outcomes each cycle have improved.